878. Antimicrobial Susceptibility of Pathogens Isolated from Surgical Site Infections in Japan: Comparison of Data from Nationwide Surveillance Studies Conducted in 2010, 2014–2015 and 2018-2019. (31st December 2020) - Takesue, Yoshio; Hanaki, Hideaki; Kusachi, Shinya; Mikamo, Hiroshige; Ueda, Takashi; Tateda, Kazuhiro; Kiyota, Hiroshi
Abstract: Background: A nationwide survey was conducted in Japan from 2018–2019 to investigate the antimicrobial susceptibility of pathogens isolated from surgical site infections (SSI). Methods: The resulting data were compared with that obtained in earlier surveys, conducted in 2010, 2014–2015, and 2018-2019. Results: Seven main organisms were collected, and in total 2081 isolates were studied. Although a significant increase of extended-spectrum β-lactamase (ESBL) producing organisms among Enterobacteriaceae was demonstrated in 2014–15 (13.5%) compared with 2010 (5.3%), the incidence remained 6.6% in 2018–19. Only one carbapenemase-producing Enterobacteriaceae isolates were identified in the 2018–2019 study. The geometric mean (GM) MICs for ESBL producing isolates in 2018–2019 were 0.08 µg/mL for meropenem, 2.67 µg/mL for tazobactam/piperacillin, 0.40 µg/mL for tazobactam/ceftolozane, 6.35 µg/mL for cefoxitin, and 1.12 µg/mL for gentamycin. Antibiotic susceptible rate in Pseudomonas aeruginosa was 95.5% in meropenem, 93.9% in piperacillin/tazobactam, 100% in tazobactam/ceftolozane, 97.0% in cefepime, 90.9% in ciprofloxacin, and 86.4% in gentamycin. There was no significant difference in methicillin resistance rate of Staphylococcus aureus isolates among 3 study periods (72.0% in 2010, 53.4% in 2014–2015, and 63% in 2018-19). MRSA isolates with a vancomycin MIC of 2μg/mL accounted for 9.7% in 2010, 1.2% in 2014–2015, and 3.1% in 2018-19. GM MICs for MRSA isolates were 2.09 µg/mL for linezolid, 0.32 µg/mL for tedizolid, and 0.61 µg/mL for daptomycin. GM MICs in linezolid and daptomycin for the isolates in 2018–19 tended to be increased compared with isolates in 2010 (1.74 to 2.09 and 0.35 to 0.61 µg/mL, respectively). More than 90% of isolates belonging to the Bacteroides fragilis group remained susceptible to tazobactam/piperacillin, meropenem, and metronidazole. In contrast, lower levels of susceptibility were observed for moxifloxacin (65.3%), cefmetazole (47.2%) and clindamycin (38.9%). In cefoxitin, non- fragilis Bacteroides isolates had lower rates of antibiotic susceptibility compared with B. fragilis . (51.3% vs. 81.8%). Conclusion: Overall, the surveillance data clarified trends in antimicrobial susceptibility for organisms commonly associated with SSI. Disclosures: Yoshio Takesue, M.D, Ph.D, Astellas Pharma Inc (Speaker's Bureau)MSD Japan (Speaker's Bureau)Sumitomo Dainippon Pharma Co. Ltd. (Grant/Research Support) Hiroshige Mikamo, M.D, Ph.D, Astellas Pharma Inc. (Grant/Research Support, Speaker's Bureau)MSD Japan (Grant/Research Support, Speaker's Bureau)Pfizer Japan Inc. (Grant/Research Support)Sumitomo Dainippon Pharma Co., Ltd (Grant/Research Support, Speaker's Bureau)